The strategic process and competitiveness of a consulting company in the year 2022, case: JC Ingeniería y Consultoría S.A.C. (Innovation & Development in Engineering and Applied Science, 2025)
This study aims to establish the level of relationship between the strategic process and the competitiveness of a consulting company in the year 2022. The results obtained from the research will allow us to determine how the strategic process is being developed in the consulting company J.C. Engineering and Consulting S.A.C. and how this impacts its competitiveness. The research will help build an effective framework to analyze, review, and measure the impact of the strategic process on business competitiveness. It is concluded that the variables 'strategic process' and 'competitiveness of a consulting company' are positively related with a correlation coefficient of 0.696. This leads to the decision to reject the null hypothesis; that is, a significant positive relationship exists between the strategic process and the competitiveness of a consulting company in 2022.
Keywords: Process; Strategic; Competitiveness; Consulting; Business